A New Low-Energy Proton Irradiation Facility to Unveil the Mechanistic Basis of the Proton-Boron Capture Therapy Approach - Valerio Ricciardi; Pavel Bláha; Raffaele Buompane; Giuseppina Crescente; Giacomo Cuttone; Lucio Gialanella; Katarina Michaličková; Severina Pacifico; Giuseppe Porzio; Lorenzo Manti (Applied Sciences, 2021)
Protontherapy (PT) is a fast-growing cancer therapy modality thanks to much-improved normal tissue sparing granted by the charged particles’ inverted dose-depth profile. Protons, however, exhibit a low biological effectiveness at clinically relevant energies. To enhance PT efficacy and counteract cancer radioresistance, Proton–Boron Capture Therapy (PBCT) was recently proposed. PBCT exploits the highly DNA-damaging α-particles generated by the p + 11B→3α (pB) nuclear reaction, whose cross-section peaks for proton energies of 675 keV. Although a significant enhancement of proton biological effectiveness by PBCT has been demonstrated for high-energy proton beams, validation of the PBCT rationale using monochromatic proton beams having energy close to the reaction cross-section maximum is still lacking. To this end, we implemented a novel setup for radiobiology experiments at a 3-MV tandem accelerator; using a scattering chamber equipped with an Au foil scatterer for beam diffusion on the biological sample, uniformity in energy and fluence with uncertainties of 2% and 5%, respectively, was achieved. Human cancer cells were irradiated at this beamline for the first time with 685-keV protons. The measured enhancement in cancer cell killing due to the 11B carrier BSH was the highest among those thus far observed, thereby corroborating the mechanistic bases of PBCT.